1998
DOI: 10.1094/mpmi.1998.11.12.1233
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exopolysaccharides of Rhizobium leguminosarum bv. viciae as Host Plant-Specific Molecules Required for Infection Thread Formation During Nodulation of Vicia sativa

Abstract: Mutants of Rhizobium leguminosarum bv. viciae bacteria that are affected in the biosynthesis of exopolysaccharides (EPS) are unable to effectively nodulate their host plants. By studying defined mutants, we show that R. legumi-nosarum bv. viciae strains require EPS for formation of infection threads in Vicia sativa (vetch) as well as for efficient induction of tight root hair curling. Results of coinoculation experiments with the EPS-deficient pssD111 mutant of R. leguminosarum bv. viciae in combination with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 60 publications
0
35
0
3
Order By: Relevance
“…If the infection thread exits the epidermal cell, it does so by fusing with the distal cell wall, and bacteria enter the intercellular space between the epidermal cell and the underlying cell layer. Invagination and tip growth, similar to those seen at the beginning of infection thread growth, occur in the underlying cell, and a thread filled with bacteria is propagated further toward the root interior (170,173,175). Branching of the thread as it grows through the root and enters the nodule primordium increases the number of sites from which bacteria can exit the thread and enter nodule cells, ensuring that a sufficient number of nodule cells are colonized.…”
Section: Brief Outline Of the Infection Process In Plants That Form Imentioning
confidence: 99%
See 3 more Smart Citations
“…If the infection thread exits the epidermal cell, it does so by fusing with the distal cell wall, and bacteria enter the intercellular space between the epidermal cell and the underlying cell layer. Invagination and tip growth, similar to those seen at the beginning of infection thread growth, occur in the underlying cell, and a thread filled with bacteria is propagated further toward the root interior (170,173,175). Branching of the thread as it grows through the root and enters the nodule primordium increases the number of sites from which bacteria can exit the thread and enter nodule cells, ensuring that a sufficient number of nodule cells are colonized.…”
Section: Brief Outline Of the Infection Process In Plants That Form Imentioning
confidence: 99%
“…However, plants that form determinate nodules do not have such a requirement (16,31,54,64,67,68,81,88,94,95,121,134,175). The roles of rhizobial exopolysaccharides in symbiotic nodulation have been most thoroughly studied in S. meliloti.…”
Section: Bacterial Contributions To Infection Threadsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that Alg14 was needed for the correct positioning of Alg13 on the cytosolic face of the endoplasmic reticulum membrane mediating the formation of the active UDP-N-acetylglucosamine transferase complex [65,66]. Mutations in the pssE and pssD genes fully abolished EPS production and as a consequence resulted in defects of nodule infection [67][68][69].…”
Section: Assembly Of the Eps Repeating Unitmentioning
confidence: 99%